АНАЛІЗ ТА ОПТИМІЗАЦІЯ ЕНЕРГОПРОЦЕСІВ У РОЗОСЕРЕДЖЕНИХ ЕЛЕКТРОЕНЕРГЕТИЧНИХ СИСТЕМАХ - Денисюк, С.П. (Інститут електродинаміки НАН України, Київ, 2016)
The features of energy processes in distributed power systems with alternative energy sources and controls devices based on power electronics optimization analysis are researched. The feasibility of power freeze decomposition and power exchange in to components that reflect a variety of factors influence are showed. The ratio for component power losses analysis, the mutual influence of the elements estimation and measurement accuracy are presented. References 5.